2009
DOI: 10.1598/jaal.52.7.6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Internet and Television Use on the Reading Habits and Practices of College Students

Abstract: The authors explore whether Internet and television use displaces other activities, including recreational reading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
74
3
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 14 publications
15
74
3
16
Order By: Relevance
“…Mokhtari, Reichard, and Gardner found that students reported spending more time on academic reading than on leisure reading or watching television, although they reported enjoying academic reading much less any other activity. 27 In contrast, students rated leisure reading as an enjoyable activity, but they did not devote much time to it. Gilbert and Fister found that most students in their study enjoyed leisure reading but that they were unable to spend time on it because of the amount of time they must spend on their academic reading.…”
Section: What Students Readmentioning
confidence: 95%
“…Mokhtari, Reichard, and Gardner found that students reported spending more time on academic reading than on leisure reading or watching television, although they reported enjoying academic reading much less any other activity. 27 In contrast, students rated leisure reading as an enjoyable activity, but they did not devote much time to it. Gilbert and Fister found that most students in their study enjoyed leisure reading but that they were unable to spend time on it because of the amount of time they must spend on their academic reading.…”
Section: What Students Readmentioning
confidence: 95%
“…A 1991 survey of over 300 seniors at a small public liberal arts institution found that 88 percent of them engaged in reading for pleasure, favoring literature and current events as subject matter. 20 A more recent study 21 of 539 students who completed time-diary surveys found that "using the Internet" was more popular with students than recreational reading, but that Internet use did not appear to displace reading as an activity. Watching television was less popular than reading for pleasure, but students were more likely to watch some television every day than to read for pleasure.…”
Section: Reading and The College Experiencementioning
confidence: 99%
“…Many studies of reading habits investigated time spent reading (Mokhtari, Reichard and Gardner, 2009), or the preferred medium for reading, such as print or digital (Zhang 2014). Many of those required students to select from a given list of types of materials.…”
Section: Introductionmentioning
confidence: 99%